Difference Between Income and Expenditure Method in Measuring Poverty in Kelantan, Malaysia. - Ali, Ahmad Fahme Mohd (International Journal of Economics, Management and Accounting, 2019)
This study attempts to identify convenient poverty assessment in Kelantan, Malaysia. It uses primary data from 546 households based on stratified multi-stage sampling process among Kelantan’s poor and needy zakat recipients who occupy the bottom decile group of living standards. The monthly expenditure and income poverty lines were used as standard of measurement to measure poverty. To address dimension of poverty this study uses three major indices of poverty, the Headcount Index, Poverty Gap Index and Sen Index. These poverty methods will analyse the poverty in terms of incidence, intensity and severity of poverty. The results show that expenditure method poverty line is 1.6 times higher than income method poverty line. The expenditure of the poor and needy in Kelantan was 1.5 times higher than their income. This study also indicates that the lowest monthly expenditure requires 31 per cent of poverty line to reach minimum level while the lowest monthly income require 83 per cent of poverty line to achieve the same level. Headcount index shows that expenditure approach estimates higher number of poor than income approach, 91 and 80 per cent of sample are under poverty line in Kelantan using expenditure and income methods, respectively. The poverty gap index was 0.51 for expenditure and 0.43 for income method in the study area. In Kelantan, on average 51 per cent of the poverty line cash transfer is needed to lift each poor person out of poverty following expenditure method. However, on average 43 per cent of the poverty line cash transfer is needed to lift each poor person out of poverty following income method.